Synthesis and structure-activity-relationship studies of thiazolidinediones as antiplasmodial inhibitors of the Plasmodium falciparum cysteine protease falcipain-2 - Sharma, Rajni Kant; Younis, Yassir; Mugumbate, Grace; Njoroge, Mathew; Gut, Jiri; Rosenthal, Philip J; Chibale, Kelly (Elsevier, 2022)
Following a structure-based virtual screening, a series of 2,4 thiazolidinediones was synthesized in order to explore structure activity relationships for inhibition of the Plasmodium falciparum cysteine protease falcipain-2 (FP-2) and of whole cell antiparasitic activity. Most compounds exhibited low micromolar antiplasmodial activities against the P. falciparum drug resistant W2 strain. The most active compounds of the series were tested for in vitro microsomal metabolic stability and found to be susceptible to hepatic metabolism. Subsequent metabolite identification studies highlighted the metabolic hot spots. Molecular docking studies of a frontrunner inhibitor were carried out to determine the probable binding mode of this class of inhibitors in the active site of FP-2.